The Urgency of Brief Training for Citizens to Search and Discover Illegal Levies at Public Institution in Indonesia - Pamuji, Wirawan; Pramudita Ananta Prabowo; Achmad Feryliyan (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The Public Institution roles a main element to gain service and supervision to all citizens in Indonesia to create and serve anything of citizens requires both services and goods. In the other hand, with the matter in this case, most of the officials perform inadequate acts with illegal levies to maintain business instead of standard instruction in committing transaction and specific affair in academicals purpose. The research is designed with Literal Data; Researcher develops arguments with Descriptive Qualitative Research.  The Subject can infer Contextual Application as how citizen discover ahead with required data to report for the security officials with Inquiry Strategy